Top-Emission Organic Light Emitting Diode Fabrication Using High Dissipation Graphite Substrate - Yu-Sheng Tsai; Lin-Ann Hong; Jian-Ji Huang; Kuan-Hung Yeh; Fuh-Shyang Juang (International Journal of Photoenergy)
This study uses a synthetic graphite fiber as the heat dissipation substrate for top-emission organic light emitting diode (TEOLED) to reduce the impact from joule heat. UV glue (YCD91) was spin coated onto the substrate as the insulation layer. The TEOLED structure is (glass; copper; graphite) substrate/YCD91 glue/Al/Au/EHI608/TAPC/Alq3/LiF/Al/Ag. The proposed graphite fiber substrate presents better luminous performance compared with glass and copper substrate devices with luminance of 3055 cd/m2 and current efficiency of 6.11 cd/A at 50 mA/cm2. When lighting period of different substrates TEOLED, the substrate case back temperature was observed using different lighting periods. A glass substrate element operating from 5 to 25 seconds at 3000 cd/m2 luminance produced a temperature rate of 1.207°C/sec. Under 4000 cd/m2 luminance the copper and graphite substrate temperature rates were 0.125°C/sec and 0.088°C/sec. Graphite component lifetime was determined to be 1.875 times higher than the glass components and 1.125 times higher than that of copper.